Bremelanotide for Female Sexual Dysfunctions in Premenopausal Women: A Randomized, Placebo-Controlled Dose-Finding Trial. (June 2016) - Clayton, Anita H; Althof, Stanley E; Kingsberg, Sheryl; DeRogatis, Leonard R; Kroll, Robin; Goldstein, Irwin; Kaminetsky, Jed; Spana, Carl; Lucas, Johna; Jordan, Robert; Portman, David J
Aim: Evaluate efficacy/safety of bremelanotide (BMT), a melanocortin-receptor-4 agonist, to treat female sexual dysfunctions in premenopausal women.Methods: Patients randomized to receive placebo or BMT 0.75, 1.25 or 1.75 mg self-administered subcutaneously, as desired, over 12 weeks. Primary end point was change in satisfying sexual events/month. Secondary end points included total score changes on female sexual function index and female sexual distress scale-desire/arousal/orgasm.Results: Efficacy data, n = 327. For 1.25/1.75-mg pooled versus placebo, mean changes from baseline to study end were +0.7 versus +0.2 satisfying sexual events/month (p = 0.0180), +3.6 versus +1.9 female sexual function index total score (p = 0.0017), −11.1 versus −6.8 female sexual distress scale-desire/arousal/orgasm total score (p = 0.0014). Adverse events: nausea, flushing, headache. Conclusion: In premenopausal women with female sexual dysfunctions, self-administered, as desired, subcutaneous BMT was safe, effective, and well tolerated (NCT01382719).